Posttesting Students To Assess the Effectiveness of Remedial Instruction in College Richard Sawyer and Jeff Schiel. - Sawyer, Richard (Distributed by ERIC Clearinghouse, 2000)
At many postsecondary institutions, there are two levels of first-year courses: a "standard" course in which most students enroll; and a "remedial" course for academically underprepared students. This paper is concerned with determining whether taking a remedial course increases the cognitive skills that students need to succeed in a standard course. The paper describes some effectiveness indicators based on data from posttesting students (i.e., testing them after they have completed a remedial course). The paper also discusses how prior selection and measurement error in the initial placement test and the posttest affect the indicators. An example is provided to illustrate the indicators and the effects of prior selection and measurement error. Pretest and posttest data were obtained from students enrolled in 9 2-year institutions and 10 4-year institutions in a state postsecondary education system in which placement decisions are made using 1 of 2 screening tests, followed in some cases by a placement test. The numbers of pretested students were 4,434 for Algebra, 8,563 for Reading, and 6,281 for Writing. Results suggest that students who completed the remedial courses offered by this group of institutions increased their academic skills. An appendix contains four propositions for approaching the data. (Contains 2 tables and 15 references.) (SLD)